(tan x)^3 + (tan x)^2 - 3(tan x) - 3 = 0

Printable View

- Apr 23rd 2014, 03:06 PMjennifernghisolve this trig equation!!!!!!!!
(tan x)^3 + (tan x)^2 - 3(tan x) - 3 = 0

- Apr 23rd 2014, 04:16 PMtopsquarkRe: solve this trig equation!!!!!!!!
- Apr 23rd 2014, 04:55 PMSorobanRe: solve this trig equation!!!!!!!!
Hello, Jennifer!

Quote:

$\displaystyle \tan^3\!x + \tan^2\!x - 3\tan x - 3 \:=\: 0$

Factor: .$\displaystyle \tan^2\!x(\tan x + 1) - 3(\tan x + 1) \:=\:0$

Factor: .$\displaystyle (\tan x + 1)(\tan^2x-3) \:=\:0$

Can you continue?